Cultivation of Family Medicinal Plants (Toga) in the Campus Teaching Program Batch V at SDN Sitanggal 04 Brebes - Hayati, Muriani Nur; Atika, Nur; Sabilla, Afida Nurul; Widiyanto, Bayu (ASEAN Journal of Empowering Community, 2023)
SDN Sitanggal 04 is one of the schools in Sitanggal Village, which is located very strategically because it is directly opposite the provincial road which is used by many public transportations. The school is also not too far from a large and busy traditional market and close to places for shopping and family recreation, so the health condition of the school's environment is very vulnerable. Therefore, the attitude of caring for the environment must be applied from an early age. One of them is through the cultivation of family medicinal plants (TOGA) in the school environment. The purpose of this service is to foster an attitude of caring for the environment in students, create a healthy school environment, provide insight and skills to students about family medicinal plants (TOGA) and how to grow them. The method used is Participatory Action Research (PAR). The results of this service show that the attitude of caring for the environment, the insights and skills of students at SDN Sitanggal 04 are increasing regarding family medicinal plants (TOGA) and their planting.